Early postoperative neuropathic pain assessed by the DN4 score predicts an increased risk of persistent postsurgical neuropathic pain. Issue 10 (October 2017) - Beloeil, Helene; Sion, Barthelemy; Rousseau, Chloe; Albaladejo, Pierre; Raux, Mathieu; Aubrun, Frederic; Martinez, Valeria
Abstract : BACKGROUND: Acute neuropathic pain can occur in the postoperative period but any link with persistent post-surgical neuropathic pain remains unclear. OBJECTIVES: The objectives of this study were to prospectively describe the incidence of acute post-surgical neuropathic pain in a large population using the DN4 (clinician administered) questionnaire and to confirm the hypothetical link between acute and persistent neuropathic pain at 2 months after surgery in a large population using the DN2 (self administered) questionnaire. DESIGN: A multi-centre, prospective and observational trial. SETTING: Two consecutive days in 27 hospitals in France. PATIENTS: Six hundred and eight patients undergoing 13 different types of surgery. Fifteen patients were excluded as data were incomplete, and 229 (38.6%) and 260 (43.8%) were not contactable for assessment at 1 and 2 months after surgery, respectively. MAIN OUTCOME MEASURES: Pain was evaluated at least 2 h postoperatively on the same day (D0), on the second day (D2) and at 1 and 2 months after surgery (M1 and M2). Pain was assessed using a 10-point Numeric Rating Scale. If the Numeric Rating Scale score was greater than 0, neuropathic pain was assessed using a DN4 (clinician administered) questionnaire or using a DN2 (self-administered) questionnaire. Acute and persistent postsurgical neuropathic pain (PPSNP) were defined respectively by a DN4 score at least 4/10 on day 0 and/or day 2 and a DN2 score at least 3/7 at 2 months after surgery. RESULTS: Of the 593 patients included, 41.2% were in pain before surgery and 8.2% described neuropathic pain. Early after surgery, the majority of the 593 patients (72.2% on the day of surgery and 71.3% on day 2) experienced acute pain. It was neuropathic in nature in 5.6% of patients (95% CI, 3.6 to 8.3) on the day of surgery and 12.9% (95% CI, 9.7 to 16.7) on day 2. Two months after surgery, PPSNP was present in 33.3% of the 333 patients assessed. Multivariate analysis showed that a DN4 score at least 4/10 on the day of surgery or on day 2 was a significant risk factor for PPSNP [odds ratios 4.22 (95% CI, 2.19 to 8.12)]. CONCLUSION: Our results suggest that early acute postsurgical neuropathic pain significantly increases the risk of persistent post-surgical neuropathic pain. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NTC NCT02826317.